Optimizing Handwashing Practices through Audiovisual-Based Health Education: A Pre-Experimental Study at Sanggar Belajar Aisyiyah Kampung Pandan, Malaysia - Firdaus, Okka Hafiizh; Syabariyah, Sitti; Fatmawati, Ariani (Journal of Public Health Sciences, 2024)
The correct practice of handwashing among preschool children remains notably deficient, consequently contributing to a heightened prevalence of infectious diseases within this age group. To ameliorate this situation, the utilization of audiovisual-based health education has been proposed as an effective means. The principal aim of this investigation is to enhance handwashing behaviors in preschool children. Employing a quantitative approach, the study adopted a pre-experimental one-group pre-test post-test research design, encompassing a sample size of 46 participants selected via a total sampling technique. Data was gathered through the utilization of observation sheets and subsequently analyzed employing the Wilcoxon Signed Ranks Test. The outcomes unveiled that, before the implementation of health education, handwashing behavior was predominantly subpar, with 95.6% of cases falling into this category. However, post-health education, the majority of cases (87%) exhibited commendable handwashing behavior. This transformation was supported by a p-value of 0.000, underscoring the substantive impact of audiovisual-based health education on handwashing practices among preschool children. It is advisable for the research site to consistently reinforce these behaviors by regularly presenting handwashing instructional videos.